City of the future Ludwigsburg: co-creation in urban development processes. - Dübner, Sven; Fanderl, Nora; Heydkamp, Constanze (My University, 2018)
In the face of the trend towards digitization, the consensus that successful urban solutions shall collectively be conceived and developed as a societal task is becoming increasingly present. [...] This paper is based on the project "City of the Future Ludwigsburg" which is funded by the German Ministry of Research and Education (BMBF) as part of the "Flagship Initiative City of the Future". Within this initiative, local stakeholders, communities, businesses, the creative industries, civil society representatives and the scientific community cooperate in Ludwigsburg in order to implement processes and recommendations for action in Germany's future cities. As part of the three-phase tendering, in the city of Ludwigsburg the first phase focused on the joint development of a comprehensive concept for the planning and implementation of a sustainable and holistic vision 2030+. Against this background, currently phase two addresses digitization and urban space amongst others by hosting three consecutive events in the so-called "Makeathon" format. They address the future of urban space and urban development with a focus on digital solutions. To carry out these events, a workshop space was implemented which is called "urban laboratory" (Stadtlabor). Within this lab innovative ideas and possible measures for "upgrading" public space are identified and evaluated with regard to their overall benefits and their potential to improve their quality. The aim of the joint research project between Fraunhofer IAO and the city of Ludwigsburg is to test the structured co-creation process as a new governance format. Thus, impulses with regards to content and processes can be given for the city administration and politics, that flow into strategies as well as plans.
Keywords: Mittelstadt; Stadtentwicklungsplanung; Planungsprozess; Bürgerbeteiligung; E-Government; Beteiligungsverfahren